Cold Ion Outflow Modulated by the Solar Wind Energy Input and Tilt of the Geomagnetic Dipole. Issue 10 (19th October 2017) - Li, Kun; Wei, Y.; André, M.; Eriksson, A.; Haaland, S.; Kronberg, E. A.; Nilsson, H.; Maes, L.; Rong, Z. J.; Wan, W. X.
Abstract: The solar wind energy input into the Earth's magnetosphere‐ionosphere system drives ionospheric outflow, which plays an important role in both the magnetospheric dynamics and evolution of the atmosphere. However, little is known about the cold ion outflow with energies lower than a few tens of eV, as the direct measurement of cold ions is difficult because a spacecraft gains a positive electric charge due to the photoemission effect, which prevents cold ions from reaching the onboard detectors. A recent breakthrough in the measurement technique using Cluster spacecraft revealed that cold ions dominate the ion population in the magnetosphere. This new technique yields a comprehensive data set containing measurements of the velocities and densities of cold ions for the years 2001–2010. In this paper, this data set is used to analyze the cold ion outflow from the ionosphere. We found that about 0.1% of the solar wind energy input is transformed to the kinetic energy of cold ion outflow at the topside ionosphere. We also found that the geomagnetic dipole tilt can significantly affect the density of cold ion outflow, modulating the outflow rate of cold ion kinetic energy. These results give us clues to study the evolution of ionospheric outflow with changing global magnetic field and solar wind condition in the history. Key Points: About 0.1% of the solar wind energy input is transformed to the hemispheric kinetic energy of cold ion outflow at the topside ionosphere The density and the total kinetic energy of cold ion outflow from the polar cap increase with increasing solar wind energy input The geomagnetic dipole tilt angle modulates the solar illumination over the polar cap, significantly affecting the outflow density